Propagation of Teak by Root Grafts - Dabral, S. L. (Indian Forester, 1977)
A non conventional technique of propagating teak clones by grafting a root from one or two year old seedling On a flowering branch, in order to get flowers and fruits in the next one or two years, has been developed and described here. The technique is simple and has been found to yield high success The technique has been described along with its special advautages. The scope of this technique haa been indicated in the end.